1997
DOI: 10.1099/00222615-46-4-321
|View full text |Cite
|
Sign up to set email alerts
|

GM-CSF-modulated phagocytosis of Trichosporon beigelii by human neutrophils

Abstract: Trichosporon beigelii has emerged as a lethal opportunist pathogen in granulocytopenic and corticosteroid-treated patients. Little is known of the host defence mechanisms against this yeast. The interaction between human neutrophils and serum-opsonised T. beigelii and the effect of GM-CSF on binding and ingestion of the yeast by neutophils were investigated by a microscopic analysis of neutrophil monolayers stained with FITCConcanavalin A. Positive staining with FITC-Concanavalin A distinguished between intrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Several reagents are known to alter the functions of neutrophils (Bharadwaj et al ., 2001; Marino et al ., 2001; Nishimura et al ., 2001). Cytokine like GM‐CSF or microbial products such as yeast glucan and zymosan might modulate the function of neutrophils (Bober et al ., 1995; Kumaratilake et al ., 1996; Richardson & Chung, 1997; Bharadwaj et al ., 2001; Wanten et al ., 2001). In the present study, we demonstrated that the polysaccharide component of Chinese medicine G. lucidum possesses capability for enhancing neutrophil functions in phagocytosis and migration.…”
Section: Discussionmentioning
confidence: 99%
“…Several reagents are known to alter the functions of neutrophils (Bharadwaj et al ., 2001; Marino et al ., 2001; Nishimura et al ., 2001). Cytokine like GM‐CSF or microbial products such as yeast glucan and zymosan might modulate the function of neutrophils (Bober et al ., 1995; Kumaratilake et al ., 1996; Richardson & Chung, 1997; Bharadwaj et al ., 2001; Wanten et al ., 2001). In the present study, we demonstrated that the polysaccharide component of Chinese medicine G. lucidum possesses capability for enhancing neutrophil functions in phagocytosis and migration.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, granulocytopenia is the most common apparent risk factor of disseminated trichosporonosis, and the resolution of infection in neutropenic patients is related primarily to bone marrow recovery. Although neutrophils are important components of the defence system against this infection [8], mononuclear cells serve as the primary source of phagocytic defence in patients with profound and prolonged neutropenia. Macrophages play an important role in host resistance to acute systemic candidiasis and to disseminated candidiasis of endogenous origin [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, given that cryptococcal GXM impairs immune function via the direct stimulation of the inhibitory FcγRIIB (Monari et al, 2006), and that genetic variants in FcγRIIIA increase the risk for human immunodeficiency virus (HIV)-associated cryptococcal disease (Rohatgi et al, 2013), it is plausible that a PTX3-FcγR axis is also in play during the immune response to trichosporonal GXM. This hypothesis is further supported by the finding that the binding and phagocytosis of T. beigelii by neutrophils was a complement-dependent process enhanced by granulocyte-macrophage colony stimulating factor (GM-CSF) (Richardson and Chung, 1997), with consequences on fungal killing (Lyman et al, 1994). M-CSF displayed comparable effects, stimulating the antifungal activity of monocytes against T. asahii , partly via the production of tumor necrosis factor (TNF)-α (Sasaki et al, 2000).…”
Section: The Trichosporon-host Interactionmentioning
confidence: 90%